2000
DOI: 10.1164/ajrccm.162.4.2003124
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance between Platelet Vascular Endothelial Growth Factor and Platelet-derived Growth Factor in Pulmonary Hypertension

Abstract: Focal vascular injury and impaired endothelial function are features of pulmonary hypertension (PH) that lead to enhanced platelet endothelial cell interactions. Vascular endothelial growth factor (VEGF) is contained in platelets and released at sites of vascular injury to promote endothelial repair and wound healing in combination with platelet-derived nonspecific mitogens such as platelet-derived growth factor (PDGF). The overall balance between platelet VEGF and PDGF was investigated in 21 patients with pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
1
7

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 21 publications
4
57
1
7
Order By: Relevance
“…In the current study, we did not find any correlation between VEGF and arterial or mixed venous oxygen saturation. Our results regarding circulating levels of VEGF agree with the findings in a previous report of elevated serum VEGF levels in peripheral venous blood samples from patients with PAH [22]. In contrast, BENISTY et al [23] showed no significant differences in circulating VEGF levels in peripheral venous blood samples between patients and control subjects.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, we did not find any correlation between VEGF and arterial or mixed venous oxygen saturation. Our results regarding circulating levels of VEGF agree with the findings in a previous report of elevated serum VEGF levels in peripheral venous blood samples from patients with PAH [22]. In contrast, BENISTY et al [23] showed no significant differences in circulating VEGF levels in peripheral venous blood samples between patients and control subjects.…”
Section: Discussionsupporting
confidence: 92%
“…Several trials have consistently shown an improvement in the exercise capacity, cardiopulmonary hemodynamics, New York Heart Association functional class, symptoms, as well as survival in patients with PAH treated with continuous infusion of intravenous prostacyclin (epoprostenol). [27][28][29] Epoprostenol infusion also improves the balance between ET-1 release and clearance, 30 increases VEGF levels, 31 and restores normal homeostasis by increasing plasma levels of soluble P-selectin and thrombomodulin, which are reportedly low in patients with PAH. 32…”
Section: Prostacyclinmentioning
confidence: 99%
“…Platelet levels of VEGF are also elevated in PH. 31 The putative role of VEGF may depend on the very nature of the normal or diseased endothelial cells. In the resting or homeostatic state, VEGF is a survival and differentiating factor for lung endothelial cells and, therefore, VEGF elevation in PH may represent a protective response.…”
Section: Vascular Endothelial Growth Factormentioning
confidence: 99%
“…Tryptophan hydroxylase (TPH), the rate-limiting enzyme in 5-HT biosynthesis, is also expressed at abnormally high levels in pulmonary endothelial cells from patients with idiopathic PAH, and therefore raises 5-HT levels locally . There is evidence that alterations in platelet 5-HT storage and/or increased platelet www.intechopen.com consumption by the lung may trigger the development of PAH (Herve et al, 1990;Herve et al, 1995;Breuer et al, 1996;Eddahibi et al, 2000b;Kereveur et al, 2000;Morecroft et al, 2005). Furthermore, serotoninergic appetite suppressant drugs have been associated with an increased risk of developing PAH (Douglas et al, 1981;Gurtner, 1985;Loogen et al, 1985;Brenot et al, 1993;Abenhaim et al, 1996;Souza et al, 2008).…”
Section: The Serotoninergic System In the Pathogenesis Of Pahmentioning
confidence: 99%